Cultural Attraction in Film Evolution: the Case of Anachronies - Sobchuk, Oleg (Journal of cognition and culture, 2020)
In many films, story is presented in an order different from chronological. Deviations from the chronological order in a narrative are called anachronies. Narratological theory and the evidence from psychological experiments indicate that anachronies allow stories to be more interesting, as the non-chronological order evokes curiosity in viewers. In this paper we investigate the historical dynamics in the use of anachronies in film. Particularly, we follow the cultural attraction theory that suggests that, given certain conditions, cultural evolution should conform to our cognitive preferences. We study this on a corpus of 80 most popular mystery films released in 1970-2009. We observe that anachronies have become used more frequently, and in a greater proportion of films. We also find that films that made substantial use of anachronies, on average, distributed the anachronies evenly along film length, while the films that made little use of anachronies placed them near the beginning and end. We argue that this can reflect a functional difference between these two types of using anachronies. The paper adds further support to the argument that popular culture may be influenced to a significant degree by our cognitive biases.